Xyz
Rozwiązane

Przedstaw w jak najprostszej postaci
4x2+1/(x+1)(x-3) + 1-5x/x-3

/ - to kreska ułamkowa



Odpowiedź :

4x²+1/(x+1)(x-3) + 1-5x/x-3= 4x²++1/(x+1)(x-3) +(1-5x)(x+1) /(x+1)(x-3) =
4x²+1+x+1-5x²-5x/(x+1)(x-3)= -x²-4x+2/(x+1)(x-3)
4x2+1 1-5x
-------------+---------=
(x+1)(x-3) x-3

4x2+1 1-5x(x+1)
-------------+---------------=
(x+1)(x-3) (x-3)(x+1)

4x2+1 1-5x2-5x
-------------+----------------=
(x+1)(x-3) (x-3)(x+1)

4x2+1+1-5x2-5x
------------------=
(x+1)(x-3)

-x2+2-5x
------------------=
(x+1)(x-3)

-x2-5x+2
------------------
(x+1)(x-3)